Polysaccharide Films/Membranes for Food and Industrial Applications - Isabel Coelhoso (Polysaccharides, 2025)
Membrane processes are extensively employed in a range of industrial and food applications. Due to growing environmental concerns and the introduction of regulatory measures, it is imperative to develop innovative membrane materials that can effectively replace petrochemical-based polymers, in line with the principles of a circular economy. The focus of this review is the use of polysaccharides for obtaining films/membranes for food and industrial applications using selected case studies. Besides the polysaccharides extracted from biomass, the valorization of agrifood residues and the use of plants adapted to arid lands (i.e., cactus) to produce polysaccharide films for food packaging is addressed. Moreover, microbial polysaccharides produced using renewable resources present a significant alternative to commercial hydrophilic membranes for gases and ethanol dehydration. To meet industry requirements, the mechanical and barrier properties of the films can be improved by the inclusion of inert impermeable fillers and/or the chemical modification of the polysaccharides. The adsorption of proteins, dyes, and pharmaceutical compounds using a cellulose-based polymer is discussed. Despite their unique characteristics, polysaccharide production costs are still higher than most synthetic polymers. This is a challenge that can be overcome by scaling up the production and by valorizing agro-industrial wastes and by-products to make the application of polysaccharide membranes/films in the food and industry sectors more widespread.